Arktická expedice na souostroví Svalbard pokračuje - Elster, Josef , 1958-; Klimešová, Jitka , 1963-; Ditrich, Oleg , 1953-
We feature an article this month on a research expedition to Svalbard, an archipelago between the Arctic Ocean, Barents Sea, Greenland Sea and Norwegian Sea. The first Czech expedition by the University of South Bohemia and of the Academy of Sciences of the Czech Republic established a research station in the vicinity of Petuniabukta, in the northern part of Billefjorden, Isfjorden, in central Svalbard, which is the northernmost part of Norway. The Interdisciplinary project, Biological and climate diversity of the central part of the Svalbard Arctic Archipelago is a member of the Network for ARCtic Climate and Biological DIVersity Studies (ARCDIV). Josef Elster, Jitka Klimešová, Oleg Ditrich.